Physical pharmacy - Attwood, David (Fasttrack, 2008)
A revision guide for students giving bullet points of basic information on physical pharmacy. This text is derived from the textbook Physicochemical Principles of Pharmacy and is designed to be used alongside it for those revision periods when time is short.